Desafios de la teología del pluralismo religioso a la fe tradicional - Vigil, José Ma. (Horizonte, 2005)
The Theology of religious pluralism (TRP) is not “a sectorial” theology or “a genitive theology”, which would theologize new subjects, that is to say one more field inside the “universa theologia”. In other words, it does offer a quantitative novelty instead of a qualitative one. TRP deals with the same subjects, but from another point of view, another “formal object”. Everything is retrieved from another order, point of view, and “paradigm”. In this way, challenges seem to be huge. Great general perspectives that have never been are effected and new challenges reappear. The author works on the selection of main changes that produce current challenges. Such Challenges are presented and justified, showing in each case its implications for theological reflexion and well as for Christian life. The core of this brief study refers to the shift of a negative to a positive evaluation of the religious pluralism, a new understanding of the Revelation, the overcoming and the abandon of the category of the “election”, the main challenges in the sensible field of christology and moral, as well as the transformation of the mission.